Sensitivity of streamflow patterns to river regulation and climate change and its implications for ecological and environmental management. (1st October 2022) - Patil, Rupesh; Wei, Yongping; Pullar, David; Shulmeister, James
Abstract: Streamflow patterns support complex ecosystem functions and services. However, the direct impacts of flow regulation and climate change on patterns of streamflow are less studied. This study aims to analyse the sensitivity of streamflow patterns to the effects of flow regulation and climate change in the Goulburn-Broken catchment in Victoria, Australia. Daily streamflow was classified into low, medium, high, and overbank flow metrics using a statistical quantile-based approach. Trends and percent changes in streamflow metrics during the 1977–2018 period were analysed, and effects of change in rainfall, regulation, and flow diversion on streamflow patterns were predicted using a generalized additive model and path analysis. Low flows and medium flows increased by 26%, and high flows and overbank flows decreased by 31% during the period between 1977 and 2018. While current river regulation and flow diversion practices would dominate future change in magnitude, duration, and frequency of the streamflow, the timing of flow metrics would be dominated by variation in rainfall. These could bring a new ecological and environmental risk to the riverine ecosystem. It is recommended to increase the duration of high flows (90–120 days) and overbank flows (10–30 days) and the frequency of overbank flows to at least once every 1–2 years during wet periods to mitigate ecological and environmental risks of climate change and flow regulation in the Goulburn-Broken catchment. Graphical abstract: Image 1 Highlights: Identify key streamflow metrics to inform river ecosystem management. A quantile-based approach for holistic assessment of streamflow patterns. Streamflow patterns more sensitive to rainfall variation than regulation and diversion. Quantiles of streamflow metrics directly linked with ecological water demands. Increased high and overbank flows are needed to manage Goulburn River ecosystems.